RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS WEB PADA SMK MA’ARIF JAKARTA - Mulyati, Sri; Taufiq, Rohmat; Prianggodo, Dyas Yudi (Jurnal Teknik, 2023)
Currently science and technology are progressing very rapidly, the development of science and technology makes humans to be able to relate to each other and get information quickly, precisely and without limits. The purpose of this Thesis Report is to provide alternatives and solutions to support work effectiveness, presenting information quickly and efficiently in the process of registering new students. The collection method in this study used observation and interview methods. Based on the observation stage previously carried out, the author decided to use the SWOT analysis method in this study to identify or evaluate observation activities. From the analysis and observations made, it can be seen that the PPDB process of SMK Ma'arif Jakarta is still manual and has not been computerized. Therefore, the author proposes by designing a website-based student registration information system. For the creation of supporting programs designed using the Unified Modeling Language (UML) method, namely designing flowcharts, use case diagrams, activity diagrams, sequence diagrams, class diagrams, and entity relationshop diagrams, then the author makes them with the laravel framework. Systems that have been analyzed and built can improve and facilitate the registration committee of new students in accessing data more quickly and accurately.Keywords: New Student Registration, Information System, SMK Ma'arif Jakarta,                        Interactive Websites, UML, RAPID.